2019
DOI: 10.1371/journal.pone.0222316
|View full text |Cite
|
Sign up to set email alerts
|

Wild pollinator activity negatively related to honey bee colony densities in urban context

Abstract: As pollinator decline is increasingly reported in natural and agricultural environments, cities are perceived as shelters for pollinators because of low pesticide exposure and high floral diversity throughout the year. This has led to the development of environmental policies supporting pollinators in urban areas. However, policies are often restricted to the promotion of honey bee colony installations, which resulted in a strong increase in apiary numbers in cities. Recently, competition for floral resources … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 61 publications
(77 reference statements)
5
106
0
2
Order By: Relevance
“…Correlative and experimental evidence alike has recently shown that, at local or regional scales, honeybees can have strong negative impacts on wild bee populations in both natural and anthropogenic scenarios (Shavit et al 2009, Lindström et al 2016, Torné-Noguera et al 2016, Magrach et al 2017, Ropars et al 2019, Valido et al 2019), and that the absence of honeybees in well-preserved natural areas is associated with increasing wild bee populations (Herrera 2019). Much of the direct or circumstantial evidence on the harmful effects of honeybees on wild bees originated in the Mediterranean Basin, which motivated the hypothesis formulated in this paper of a possible replacement of wild bees by honeybees in the Mediterranean running parallel to the increasing abundance of honeybees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlative and experimental evidence alike has recently shown that, at local or regional scales, honeybees can have strong negative impacts on wild bee populations in both natural and anthropogenic scenarios (Shavit et al 2009, Lindström et al 2016, Torné-Noguera et al 2016, Magrach et al 2017, Ropars et al 2019, Valido et al 2019), and that the absence of honeybees in well-preserved natural areas is associated with increasing wild bee populations (Herrera 2019). Much of the direct or circumstantial evidence on the harmful effects of honeybees on wild bees originated in the Mediterranean Basin, which motivated the hypothesis formulated in this paper of a possible replacement of wild bees by honeybees in the Mediterranean running parallel to the increasing abundance of honeybees.…”
Section: Discussionmentioning
confidence: 99%
“…S1, Potts et al 2010, vanEngelsdorp and Meixner 2010, Moritz and Erler 2016). Honeybees have been repeatedly shown to have negative impacts on wild bee populations in both natural and anthropogenic scenarios (Goulson and Sparrow 2009, Shavit et al 2009, Lindström et al 2016, Torné-Noguera et al 2016, Magrach et al 2017, Ropars et al 2019, Valido et al 2019). I thus formulated the hypothesis that, if the abundance of managed honeybees has been actually increasing in the Mediterranean Basin over the last decades, then a profound biome-wide alteration in the proportional composition of bee pollinator assemblages could be currently underway there, involving a gradual replacement of wild bees by honeybees in flowers.…”
Section: Introductionmentioning
confidence: 99%
“…Pollinators, on the other hand, have captured the public imagination and their ecological function is well understood by non‐experts. Public enthusiasm for saving bees, however, is almost entirely focused on honey bees with an unsustainable proliferation of urban beekeeping that may actually do more harm to bee conservation than good (Ropars, Dajoz, Fontaine, Muratet, & Geslin, 2019). Furthermore, bee conservation has overlooked the critical contributions of trees through provision of pollen, nectar, and nesting sites (Baldock et al., 2015, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a common management intervention in Danish national parks is to establish hives of honey bee Apis mellifera for honey production, commonly claimed to have the added benefit of ensuring efficient pollination of native plants (Huryn 1997). However, honey bees may decrease the abundance of native threatened pollinators via competition for floral resources (Ropars et al 2019). If interactions are specialised, such that native insects are more efficient pollinators of native plants, the presence of honey bees may weaken naturally occurring interactions (do Carmo et al 2004), with negative effects on the community and ultimately the long‐term management goals that were the original rationale for establishing the national parks.…”
Section: Integrating Interaction‐focused Management In Current Practicementioning
confidence: 99%